2006
DOI: 10.1007/s00427-006-0123-2
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish orthopedia (otp) is required for isotocin cell development

Abstract: Several behavioral and physiological processes such as social, sexual, and maternal behaviors, learning and memory, and parturition are influenced by the neurohypophysial peptide oxytocin. Studies in knockout mice have identified four transcriptional regulatory genes that are required for oxytocin neuronal development in the hypothalamus. These are the basic helix-loop-helix PAS genes Single-minded 1 (Sim1) and Arylhydrocarbon receptor nuclear translocator 2 (Arnt2), the POU homeobox gene Pou3f2, and the paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 54 publications
1
57
1
1
Order By: Relevance
“…Not all the neurons in the PO depend on Arnt2/Sim1 function, as only one of two SST-expressing groups in the PO is reduced and DA neurons form normally in the PO. Combined with a recent study, which shows the requirement of Sim1 for ITNP-and VSNP-producing cells in the PO (Eaton and Glasgow, 2006;Eaton and Glasgow, 2007), our data establish that the specification of specific neurosecretory cell types of the hypothalamus is largely conserved in zebrafish. The mammalian Otp and Arnt2/Sim1 pathways eventually merge at the level of Pou3f2/Brn2.…”
Section: Research Articlesupporting
confidence: 82%
See 2 more Smart Citations
“…Not all the neurons in the PO depend on Arnt2/Sim1 function, as only one of two SST-expressing groups in the PO is reduced and DA neurons form normally in the PO. Combined with a recent study, which shows the requirement of Sim1 for ITNP-and VSNP-producing cells in the PO (Eaton and Glasgow, 2006;Eaton and Glasgow, 2007), our data establish that the specification of specific neurosecretory cell types of the hypothalamus is largely conserved in zebrafish. The mammalian Otp and Arnt2/Sim1 pathways eventually merge at the level of Pou3f2/Brn2.…”
Section: Research Articlesupporting
confidence: 82%
“…4D-F). A requirement for sim1 in specification of zebrafish itnp-and vsnp-expressing neurons has already been suggested (Eaton and Glasgow, 2006;Eaton and Glasgow, 2007). In arnt2 m1055 mutants, as in sim1a morphants, itnp and vsnp neurons in the preoptic region were strongly reduced or absent (Fig.…”
Section: Arnt2mentioning
confidence: 62%
See 1 more Smart Citation
“…The function of hypothalamic regulators seems to have been highly conserved during evolution and zebrafish orthologs have similar roles to their mouse counterparts (Machluf et al, 2011). For example, zebrafish Otp and Sim1/Arnt2 are required for the development and function of neuroendocrine cells as well as for the development of diencephalic dopaminergic (DA) neurons (Amir-Zilberstein et al, 2012;Blechman et al, 2007;Del Giacco et al, 2006;Eaton and Glasgow, 2006;Eaton and Glasgow, 2007;Eaton et al, 2008;Löhr et al, 2009;Ryu et al, 2007). Zebrafish otpb is regulated by the zinc-finger protein Fezf2 (Blechman et al, 2007), which was originally identified as a factor upregulated by overexpression of Dkk1 in zebrafish (Hashimoto et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The homeodomain transcription factor Orthopedia (Otp) is co-expressed with the two PAS domain factors Sim1 and Arnt2, the latter two forming functional heterodimers. Otp/Sim1/Arnt2-dependent cell lineages in mammals (Acampora et al, 1999;Michaud et al, 2000;Michaud et al, 1998;Wang and Lufkin, 2000) and zebrafish (Blechman et al, 2007;Del Giacco et al, 2006;Eaton and Glasgow, 2006;Eaton and Glasgow, 2007;Löhr et al, 2009;Ryu et al, 2007) include neuroendocrine cells characterised by expression of the peptide hormones corticotropin-releasing hormone, thyrotropin-releasing hormone, arginine vasopressin, oxytocin and somatostatin. In addition to neuroendocrine lineages, Otp/Sim1/Arnt2 have been shown to control development of hypothalamic A11-type dopaminergic (DA) neurons in zebrafish and, for Otp, mammals (Borodovsky et al, 2009;Löhr et al, 2009;Ryu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%